O uso de big data na fiscalização tributária de mercadorias em trânsito no Distrito Federal - Boccanera, Hermógenes Lourival Costa (2024)
This work explores the intersection between Tax Law and Information Technology, focusing on the application of Big Data in tax inspection. Initially, the basic foundations of Tax Law will be presented, including the role of the State in tax activity, tax obligations and the constitutional principles that govern taxation, with special attention to ICMS. Next, we will show an analysis of SPED that covers electronic tax documents such as NF-e, CT-e and MDF-e, highlighting the digitalization of tax obligations and the possibilities created when migrating this data to electronic media. The dissertation advances to the discussion of data science technologies, detailing concepts such as Big Data, Data Warehouses, Data Lakes and ETL processes. The application of these technologies in the processing and analysis of large volumes of tax data is demonstrated as an effective tool for identifying tax inconsistencies and evasion. Finally, we will address a case study at the Federal District Finance Department, the Electronic System for Tax Inspection in Transit (SEFIT), which illustrates the practical application of Big Data in the tax inspection of goods in transit through data crossing. The challenges faced before implementing SEFIT, the benefits of the adopted solution and the system architecture will be presented.